A prospective clinical evaluation of a patient isolation hood during the COVID-19 pandemic. Issue 1 (January 2022) - McGain, Forbes; Bates, Samantha; Lee, Jung Hoon; Timms, Patrick; Kainer, Marion A.; French, Craig; Monty, Jason
Abstract: Background: Healthcare workers (HCWs) have frequently become infected with severe acute respiratory syndrome coronavirus 2 whilst treating patients with coronavirus disease 2019 (COVID-19). A variety of novel devices have been proposed to reduce COVID-19 cross-contamination. Objectives: The aim of the study was (i) to test whether patients and HCWs thought that a novel patient isolation hood was safe and comfortable and (ii) to obtain COVID-19 infection data of hospital HCWs. Methods: This is a prospective cohort study of 20 patients, entailing HCW/patient questionnaires and safety aspects of prototype isolation hoods. COVID-19 data of HCWs were prospectively collected. Assessment of the hood's safety and practicality and adverse event reporting was carried out. Outcome measures: The outcome measures are as follows: questionnaire responses, adverse event reporting, rates of infections in HCWs during the study period (20/6/2020 to 21/7/2020), and COVID-19 infections in HCWs reported until the last recorded diagnosis of COVID-19 in HCWs (20/6/2020 to 27/9/2020). Results: Of the 64 eligible individual HCW surveys, 60 surveys were overall favourable (>75% questions answered in favour of the isolation hood). HCWs were unanimous in perceiving the hood as safe (60/60), preferring its use (56/56), and understanding its potential COVID-19 cross-contamination minimisation (60/60). All eight patients who completed the questionnaire thought the isolation hood helped prevent COVID-19 cross infection and was safe and comfortable. There were no reported patient safety adverse events. The COVID-19 attack rate from 20/6/2020 to 27/9/2020 among registered nurses was as follows: intensive care units (ICUs), 2.2% (3/138); geriatric wards, 13.2% (26/197); and COVID-19 wards, 18.3% (32/175). The COVID-19 attack rate among medical staff was as follows: junior staff, 2.1% (24/932); senior staff, 0.7% (4/607); aged care/rehabilitation, 6.7% (2/30); and all ICU medical staff, 8.6% (3/35). Conclusions: The isolation hood was preferred to standard care by HCWs and well tolerated by patients, and after the study, isolation hoods became part of standard ICU therapy. There was an association between being an ICU nurse and a low COVID-19 infection rate (no causality implied). ICU HCWs feel safer when treating patients with COVID-19 using an isolation hood.